2020
DOI: 10.1080/13811118.2020.1823916
|View full text |Cite
|
Sign up to set email alerts
|

Young Peoples’ Perspectives on the Role of Harm Reduction Techniques in the Management of Their Self-Harm: A Qualitative Study

Abstract: London. She has previous clinical experiences working with children and high-risk adolescents in community settings and within the NHS. Her research interests include self-harm, suicidality, mental health and education, and child and adolescent mental health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…Our findings suggest that the majority of people with records reporting harm minimisation find it helpful; this is consistent with previous studies reporting patients’ and practitioners’ positive opinions on harm minimisation and the need to be flexible when approaching self-harm behaviour. 24 , 27 However, the British study described above reported that 7% of participants using harm-minimisation approaches perceived them as ineffective or unhelpful. 26 Another, recent UK-based study interviewed 126 adolescents in the community aged between 11- and 21-years-old and found a third perceived harm minimisation as helpful, a third were indifferent and a third perceived harm minimisation as unhelpful.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our findings suggest that the majority of people with records reporting harm minimisation find it helpful; this is consistent with previous studies reporting patients’ and practitioners’ positive opinions on harm minimisation and the need to be flexible when approaching self-harm behaviour. 24 , 27 However, the British study described above reported that 7% of participants using harm-minimisation approaches perceived them as ineffective or unhelpful. 26 Another, recent UK-based study interviewed 126 adolescents in the community aged between 11- and 21-years-old and found a third perceived harm minimisation as helpful, a third were indifferent and a third perceived harm minimisation as unhelpful.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the views of professionals and carers over which techniques are regarded as ‘safer’ or less controversial. 27 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations